Air-conditioning cost saving and CO2 emission reduction prospective of buildings designed with PCM integrated blocks and roofs. (December 2021) - Arumugam, Chelliah; Shaik, Saboor
Abstract: The phase change materials (PCMs) in building envelopes effectively reduce cooling loads in buildings. This work explores the thermoeconomic performance of buildings designed with PCM integrated hollow concrete blocks and hollow roofs. The five PCMs were considered, such as HS24 (Hydrated salt), OM21 (organic mixtures), OM30, OM35, and OM46. Thirty various building models are studied with three configurations of PCM integrated concrete blocks (Inner side PCM layer (W-1), Center PCM layer (W-2), and Outer side PCM layer (W-3)) and two configurations of PCM integrated roof tiles (Inner side PCM layer (R-1) and outer side PCM layer (R-2)). The OM30 PCM integrated composite wall and roof tile showed better thermoeconomic performance than other studied PCMs. The building model configuration (BC-F), which is the combination of PCM composite wall (W-3) and PCM roof tile (R-2) exhibited the highest yearly air conditioning cost-saving and the highest yearly carbon emission mitigation in both hot-dry (Jodhpur) and composite (New Delhi). In the hot-dry climate, the building model configuration (BC-F) with OM30 PCM exhibited the highest air-conditioning cost savings with reasonable payback periods and highest CO2 emission reductions compared to other building model configurations studied.